Development and characterization of sulfonated polyethersulfone for proton exchanfe membrane fuel cell application - Mohd Norazam, Md Aris (2009)
Sulfonated polyethersulfone (SPES) with 20% concentration by weight were prepared with concentrated sulfonic acid at room temperature. Membrane solution developed in this study consisted of polyethersulfone dissolved in N,N – Dimethylformamide (DMF) as solvent, fuming sulfuric acid (36%) and concentrated sulfuric acid (95%-97%) as the sulfonating agent. The solution was cast manually at temperature between 25oC-28 oC. The investigation on water uptake, TGA, CHNOS elemental analysis, and FTIR has been conducted. Successful introduction of the sulfonated groups was confirmed by using the FTIR spectra in the wave number range 1020cm-1-1030 cm-1 which attributed to the symmetrical stretch of the sulfonated group. It was found that sulfonated membrane produced from mixed sulfonating agent (98% H2SO4 and 36% H2SO4.SO3) have higher degree of swelling. The type and ratio of the sulfonating agent has been identified as one of the most influential parameter in determining the bonding of -HCO3 as well as the membrane performance thus, producing different morphology. The parameter such as sulfonating agent ratio and type used strongly affects the membrane performance.